PENGARUH BENTUK HUTAN KOTA TERHADAP KENYAMANAN TERMAL DI SEKITAR HUTAN KOTA - Rizki Alfian; Tati Budiarti; Nizar Nasrullah (BUANA SAINS, 2016)
Implementing urban forest in city’s planning is an effective and efficient ways to solve ecological problems, including Malang City. There are three urban forests in Malang City (1) Malabar; (2) Velodrome; and (3) Jalan Jakarta Urban Forest. On macro scale, urban forest expected to be as a microclimate function. Microclimate could affect the human thermal comfort. The aims of this study are (1) to identify density, frequence and dominance of vegetation, (2) to analyse the correlation between urban forest shape with urban environmental thermal comfort; and (2) to evaluate the community’s perception and preference related with urban forest’s comfort. This study was held in Malang City forests. The steps for this study were (1) preparation; (2) inventory and observation; (3) measuring the thermal components; and (4) social data. The results of this study were (1) Malang City urban forests has grouped, scattered, and striped shape with multiple strata; (2)there is a positive correlation between dominance factor with comfort; (3)Temperature analysis showed that distance was not affected the temperature significantly; (4) based on visitor’s perception, urban forests in Malang regarding as comfortable urban forest but to narrow; and(5) based on community perception and preference, they want the urban forests in Malang designed proportionally with more variety kind of plants.